(untitled) (Jurnal Riset Agribisnis dan Peternakan, 2024)
Pindang eggs are one of the egg preservation and processing techniques. The material used for making pindangh eggs is a material that contains tannins. The purpose of this study was to determine the effect of various tanners on the organoleptic test of pindang eggs. The results of this study are expected to be information material for producers about the influence of various kinds of tanners on organoleptic tests of pindang eggs. The material in this study is chicken eggs, tanning ingredients, namely: tea leaves, onion skin, teak leaves, guava leaves, coconut fibers, salt, water and bay leaves. The study used was an experiment with a complete randomized design. The results of this study show that making pindang eggs with various tannery ingredients shows a real influence on the taste, color of egg whites, color of egg yolks and smell of pindang eggs. The conclusion of this study is that there is a real influence of various tanners from tea, onion peel, teak leaves, guava leaves and coconut fibers on the taste, color of egg whites, color of egg yolks and smell of pindang eggs. It is recommended that in making pindang eggs, you should use a tanner from tea because it provides the most preferred results for consumers.